Apoptosis and human reproduction - (:unkn) unknown (My University, 1997)
Apoptosis is a descriptive term to describe a type of cell death with morphological changes distinct from necrosis. It acts in a programmed manner and through this mechanism the body deletes unwanted cells without eliciting any immune response or inflammatory reaction. In human reproductive tract, recent data demonstrate that it plays an important role in some physiologic events like, the perinatal loss of germ cells, the process of follicular atresia during normal menstrual life and menopause, the regression of corpus luteum, the cyclic shedding of endometrium and some beneficial effects on the decidua during early pregnancy and later in placenta. With the further understanding of the exact mechanisms, it will guide us to solve some common clinical problems and promote the human reproductive functions.
Keywords: Apoptosis; Human reproduction